A day full of math games & activities. Find one near you.

A day full of math games & activities. Find one near you.

A day full of math games & activities. Find one near you.

A day full of math games & activities. Find one near you.

# Which expression does not factor?

m^{3} + 1

m^{3} - 1

m^{2} + 1

m^{2} - 1

**Solution:**

m^{3} + 1

Let us make use of the formula

a^{3} + b^{3 }= (a + b) (a^{2} - ab + b^{2})

Here a = m and b = 1

m^{3} + 1 = (m + 1) (m^{2} - m + 1)

m^{3} - 1

Let us make use of the formula

a^{3} - b^{3 }= (a - b) (a^{2} + ab + b^{2})

Here a = m and b = 1

m^{3} - 1 = (m - 1) (m^{2} + m + 1)

m^{2} + 1

It cannot be factored

m^{2} - 1

Let us make use of the formula

a^{2} - b^{2 }= (a + b) (a - b)

Here a = m and b = 1

m^{2} - 1 = (m + 1) (m - 1)

Therefore, m^{2} + 1 does not factor.

## Which expression does not factor?

**Summary:**

The expression m^{2} + 1 does not factor.

Math worksheets and

visual curriculum

visual curriculum